Changes of the thiol levels in the corneas of the diabetic rats: effect of carnosine, aspirin and a combination eye drops - Shi, Qiong (International Journal of Ophthalmology Press, 2010)
AIM: To investigate the effect of carnosine (Car), aspirin (Asp) and a combination of Car and Asp eye drops on the change of the thiol contents from glutathione (GSH) and protein in the corneas of the diabetic rats. METHODS: All the animals were randomly divided into five groups. The normal control group received injections of vehicle only. Diabetes was induced by injection of streptozotocin (STZ) in the Sprague-Dawley (SD) rats. The untreated group rats received only the vehicle solution (the placebo). One treated group rats were treated by instillation of one drop of 10g/L Car eye drops, another were treated by 0.5g/L Asp eye drops and the last group were treated alternately by Car 10g/L and Asp 0.5g/L eye drops for a period of 8 weeks. At the end of 8 weeks, the animals were killed and the thiols contents in the corneas were investigated. RESULTS: About 15.6% of the rats (blood glucose measured <14mmol/L) were rejected. In the corneas, the levels of thiols were declined in the untreated, Asp-treated group and combination-treated group, but they went up in Car-treated group. The levels of thiols in the Car-treated groups were much higher than that in the untreated group, and there was statistically significant difference between them (P<0.05). CONCLUSION: The results indicated that diabetes decreases the levels of thiols (from GSH and proteins) in the cornea. The Car eye drops in our study may protect the cornea against the oxidative damage caused by diabetes. And the combination eye drops also may have a certain protection for the diabetic corneas.